Pengembangan Assesment Pembelajaran pada Nilai Karakter untuk Menghadapi Era Sustainable Development Goals - Rozhana, Kardiana Metha; Sari, Nila Kartika (Universitas Nusantara PGRI Kediri, 2019)
The purpose of research and development is to produce learning assessment products based on character values ​​that have validity, applicability, and legibility. Research and development methods use the O'Malley & Pierce model which is devoted to developing learning assessments, namely: building a team, setting goals, setting results targets, conducting staff development, collecting assessment examples, adjusting existing assessments or developing new, assessment trials. and review assessment. The results of the character aspect validation showed that the criteria were very valid and could be used without revision (93%), the results of the language aspect validation showed very valid criteria and could be used without revision (93.8%). The results of the applicability test showed very good can be used without revision (88.2%). Whereas the legibility test shows very interesting criteria (97.2%) according to the conversion of the validity level, that is almost the entire contents of the assessment book is easy to understand. This product only consists of each of the 4 character values ​​developed in each lesson, this development is arranged only on theme 7 grade IV SD.